Effectiveness of Edamame Extract (Glycine max L. Merril) Against Streptococcus mutans on Orthodontic Appliances Base - Leliana Sandra Devi; Dyah Setyorini; Hanifah Syifa Hasna; Vanda Ramadhani (Humanistic Network for Science and Technology (HNST), 2023)
One of the important components in removable orthodontic appliances is the base. The material that is often used as a base is self-cured or autopolymerized acrylic resin (Orthoresin). The base of orthodontic appliances will always be in contact with saliva and become a place of attachment for microorganisms, besides that on the base of removable orthodontic appliances there are two surfaces, namely the unpolished base surface that facing the mucosa and the polished base surface. This unpolished surface causes the surface to become rough so that it can increase the accumulation of dental plaque and become a retention factor for bacteria to stick to one of them is Streptococcus mutans. Therefore, it is possible to prevent bacterial colonization with organic or non-organic inhibitors. denture cleaning by immersing the denture in a cleaning solution containing a disinfectant. This research used organic material to be used as an inhibitor with antibacterial content, namely edamame (Glycine max L. Merril). As conclusion, edamame extract with concentrations of 50% and 75% effective in inhibiting the growth of S. mutans on the basis of removable orthodontic appliances. Keywords: edamame extract; S. mutans; orthodontic appliance base